Erector Spinae Plane Block Performed in the Emergency Department for Abdominal Pain: A Case Series - Daniel Parsons-Moss; David Martin; Maribel Condori; Andrea Dreyfuss (Clinical Practice and Cases in Emergency Medicine, 2023)
Introduction: Ultrasound-guided nerve blocks are fast becoming a core part of opioid-sparing, multimodal, acute pain management in the emergency department (ED) setting. The ultrasound-guided erector spinae plane block (ESPB) has been shown to be effective in treating a variety of musculoskeletal and neuropathic painful conditions in the ED. Case Series: Here we report the effective use of the ESPB for pain control in four patients who presented with acute abdominal pain related to biliary obstruction in a resource-limited setting. Conclusion: The ESPB may be helpful in treating abdominal pain related to biliary obstruction, which is a novel indication for this well-established technique. This application is particularly relevant in resource-limited settings with significant delay in definitive surgical management. Further research is needed prior to widespread adoption.